Preparation method of nano composite flame retardant with alkali metal silsesquioxane particles loaded on surfaces of carbon nanotubes

By loading alkali metal silicon sesquioxane particles on the surface of carbon nanotubes, the problem of limited improvement in flame retardant performance caused by entanglement and agglomeration of carbon nanotubes is solved, and more efficient flame retardant performance of composite materials is achieved.

CN119410027AActive Publication Date: 2025-02-11SHANXI TAIXIN PLASTIC PROD

Patent Information

Application Number
CN202411426724.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-14
Publication Date
2025-02-11
Estimated Expiration
2044-10-14

AI Technical Summary

Technical Problem

Because of its elongated tubular structure, carbon nanotubes are prone to entanglement and agglomeration, resulting in limited improvement in flame retardant performance in composite materials.

Method used

By loading alkali metal silsesquioxane particles on the surface of carbon nanotubes, an electrostatic interaction was used to successfully prepare a nanocomposite flame retardant on the surface of carbon nanotubes.

Benefits of technology

It effectively prevents agglomeration between multiple nanotubes, improves the flame retardant performance of composite materials, and maintains the structural thermal stability of nanotubes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119410027A_ABST
    Figure CN119410027A_ABST
Patent Text Reader

Abstract

The invention relates to the field of nano-composite flame retardants, in particular to a preparation method of a nano-composite flame retardant with alkali metal silsesquioxane particles loaded on the surface of a carbon nano tube, which comprises the following steps: adding an organic solvent and the carbon nano tube into a reaction container, performing ultrasonic and mechanical stirring, adding alkali metal silsesquioxane powder into the reaction container, and performing stirring to obtain a nano-composite flame retardant; a grey black mixed solution is obtained; and carrying out suction filtration on the mixed solution, and drying the obtained filter cake to prepare the nano composite flame retardant with alkali metal silsesquioxane particles loaded on the surface of the carbon nano tube. The product prepared by the invention still presents a one-dimensional nanotube shape, the structure thermal stability of the product is good, the surface of the prepared nanotube is rough on the premise of keeping the one-dimensional nanotube microstructure, agglomeration among a plurality of nanotubes is effectively prevented, and the performance of the nanotube is improved. And the flame retardant is a nano composite flame retardant with dual excellent characteristics of the carbon nano tube and the metal silsesquioxane.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of nano composite flame retardants, and in particular to a method for preparing a nano composite flame retardant of alkali metal silsesquioxane particles loaded on the surface of carbon nanotubes. Background Art

[0002] Polyhedral oligomeric silsesquioxane (POSS) is a commonly used high-efficiency silicon-based organic-inorganic hybrid nano-scale flame retardant. POSS molecules have a precise cage-like nanostructure composed of Si-O-Si, and the molecular particle size is 1~3 nanometers. When POSS is introduced into the polymer matrix, the Si-O-Si rigid skeleton helps to produce a high-quality carbon layer during the combustion of the polymer, and the side chain organic group can improve the compatibility of POSS with the polymer matrix. The introduction of alkali metal elements into POSS can achieve a relatively excellent smoke suppression effect, which is one of the current research hotspots in the field of organic-inorganic hybrid materials science.

[0003] As a common carbon nanomaterial, carbon nanotubes are often used as flame-retardant nanofillers in polymers due to their high thermal stability and excellent mechanical properties. The effectiveness of carbon nanotubes is mainly due to the protective carbon layer formed during the combustion process, which effectively reduces the heat release during the combustion of composite materials. However, carbon nanotubes are easily entangled by their slender tubular structure and the van der Waals force between different nanotubes, which makes them tend to aggregate together, and the improvement of the flame retardant properties of the prepared composite materials is very limited.

[0004] Loading POSS nanoparticles on the surface of one-dimensional carbon nanotubes can form an "obstacle" and effectively prevent the aggregation of multiple slender tubes. Therefore, loading POSS nanoparticles on the surface of one-dimensional carbon nanotubes can effectively hinder the aggregation between different nanotubes and prevent the aggregation between individual POSS molecules. However, there are few studies on the nanocomposite system of carbon nanotubes and POSS particles. Summary of the invention

[0005] The present invention aims to provide a method for preparing a carbon nanotube surface-loaded alkali metal silsesquioxane particle nanocomposite flame retardant (CNT-POSS(Li)). The present invention uses two alkaline alkali metal silsesquioxanes (Li-Ph-POSS and Na-Ph-POSS) and commercial carbon nanotubes with carboxyl groups on the surface as raw materials, and successfully prepares a carbon nanotube surface-loaded alkali metal silsesquioxane particle nanocomposite flame retardant through electrostatic interaction.

[0006] The present invention is achieved through the following technical scheme: a method for preparing a carbon nanotube surface-loaded alkali metal silsesquioxane particle nanocomposite flame retardant, comprising the following steps: An organic solvent and carbon nanotubes are added to a reaction container, the water bath temperature is controlled to be 40-60 ºC, the ultrasonic power is 50-100 W, and mechanical stirring is continued for 0.5-1 h. Then, alkali metal silsesquioxane powder is added to the reaction container. The reaction time is 4-12 h to obtain a gray-black mixed solution. The mixed solution is filtered, and the obtained filter cake is dried to obtain a carbon nanotube surface-loaded alkali metal silsesquioxane particle nanocomposite flame retardant.

[0007] As a further improvement of the technical solution of the present invention, the mass ratio of the carbon nanotubes to the alkali metal silsesquioxane powder is (0.5-1):(1.2-3.6).

[0008] As a further improvement of the technical solution of the present invention, the organic solvent is one or more of methanol, ethanol, isopropanol, acetone, butanone, tetrahydrofuran, dichloromethane, chloroform, and dimethyl sulfoxide.

[0009] As a further improvement of the technical solution of the present invention, the mass volume ratio of the carbon nanotubes to the organic solvent is 1-3: 150-500, and the specific ratio is (1-3) g: (150-500) mL. The mass volume ratio of the alkali metal silsesquioxane powder to the organic solvent is 2-9: 100-400, and the specific ratio is (2-9) g: (100-400) mL.

[0010] As a further improvement of the technical solution of the present invention, the carbon nanotubes are carboxylated single-walled carbon nanotubes or multi-walled carbon nanotubes.

[0011] As a further improvement of the technical solution of the present invention, the alkali metal silsesquioxane is heptaphenylsilsesquioxane lithium salt or heptaphenylsilsesquioxane sodium salt.

[0012] The method for preparing a carbon nanotube surface-loaded alkali metal silsesquioxane particle nanocomposite flame retardant provided by the present invention has the following advantages compared with the prior art: The organic solvent selected by the present invention can be recycled and reused, thereby reducing costs. The reaction process is simple to operate, the conditions are relatively mild, the repeatability is good, and it has the advantages of high yield and short synthesis cycle. The prepared product still presents a one-dimensional nanotube morphology, and the product has good structural thermal stability. Under the premise of maintaining the one-dimensional nanotube micromorphology, the surface of the prepared nanotube is roughened, and the agglomeration of multiple nanotubes is effectively prevented. It is a nano composite flame retardant with dual excellent properties of carbon nanotubes and metal silsesquioxane. The present invention will provide a new strategy for the diversified preparation of high-efficiency nano-scale composite flame retardants. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the invention and, together with the description, serve to explain the principles of the invention.

[0014] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0015] Figure 1 It is the structural formula of the reaction raw material heptaphenylsilsesquioxane lithium salt.

[0016] Figure 2 It is the structural formula of the reaction raw material heptaphenylsilsesquioxane sodium salt.

[0017] Figure 3 Schematic diagram of the microscopic morphology of alkali metal silsesquioxane particle nanocomposite flame retardant (CNT-POSS(Li)) loaded on the surface of carbon nanotubes.

[0018] Figure 4 FT-IR spectra of the raw materials carboxylated multi-walled carbon nanotubes (MWCNTs-COOH), Li-Ph-POSS and the prepared nanocomposite (CNT-POSS(Li)) in Example 1.

[0019] Figure 5 The XRD spectra of the raw materials carboxylated multi-walled carbon nanotubes (MWCNTs-COOH), Li-Ph-POSS and the prepared nanocomposite (CNT-POSS(Li)) in Example 1.

[0020] Figure 6 TG spectra (nitrogen atmosphere) of the raw materials carboxylated multi-walled carbon nanotubes (MWCNTs-COOH), Li-Ph-POSS and the prepared nanocomposite (CNT-POSS(Li)) in Example 1.

[0021] Figure 7 The scanning electron microscope and corresponding element surface scan of the nanocomposite (CNT-POSS(Li)) prepared in Example 1. DETAILED DESCRIPTION

[0022] In order to more clearly understand the above-mentioned objectives, features and advantages of the present invention, the scheme of the present invention will be further described below. It should be noted that the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.

[0023] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein; it is obvious that the embodiments in the specification are only part of the embodiments of the present invention, rather than all of the embodiments.

[0024] The present invention provides a specific embodiment of a method for preparing a carbon nanotube surface-loaded alkali metal silsesquioxane particle nanocomposite flame retardant, comprising the following steps: An organic solvent and carbon nanotubes are added to a reaction container, the water bath temperature is controlled to be 40-60 ºC, the ultrasonic power is 50-100 W, and mechanical stirring is continued for 0.5-1 h. Then, alkali metal silsesquioxane powder is added to the reaction container. The reaction time is 4-12 h to obtain a gray-black mixed solution. The mixed solution is filtered, and the obtained filter cake is dried to obtain a carbon nanotube surface-loaded alkali metal silsesquioxane particle nanocomposite flame retardant.

[0025] In one embodiment provided by the present invention, the mass ratio of the carbon nanotubes to the alkali metal silsesquioxane powder is (0.5-1):(1.2-3.6).

[0026] In another embodiment provided by the present invention, the organic solvent is one or more of methanol, ethanol, isopropanol, acetone, butanone, tetrahydrofuran, dichloromethane, chloroform, and dimethyl sulfoxide.

[0027] In the present invention, the organic solvent may be added to the reaction container in steps, specifically: a portion of the organic solvent is added when the carbon nanotubes are added, and a portion of the organic solvent is added when the alkali metal silsesquioxane powder is added.

[0028] In one embodiment provided by the present invention, the mass volume ratio of the carbon nanotubes to the organic solvent is 1-3:150-500, specifically (1-3) g:(150-500) mL. The mass volume ratio of the alkali metal silsesquioxane powder to the organic solvent is 2-9:100-400, specifically (2-9) g:(100-400) mL.

[0029] In another embodiment provided by the present invention, the carbon nanotubes are carboxylated single-walled carbon nanotubes or multi-walled carbon nanotubes.

[0030] In one embodiment provided by the present invention, the alkali metal silsesquioxane is heptaphenylsilsesquioxane lithium salt or heptaphenylsilsesquioxane sodium salt. Figure 1 and Figure 2 .

[0031] The specific embodiments of the present invention are described in detail below. Example 1

[0032] A method for preparing a carbon nanotube surface-loaded alkali metal silsesquioxane particle nanocomposite flame retardant comprises the following steps: Weigh 3 g of carboxylated multi-walled carbon nanotubes (MWCNTs-COOH) and add them to a three-necked round-bottom flask. Then add 300 ml of anhydrous ethanol as a solvent. Cover the three-necked round-bottom flask and start ultrasonic heating to 45 °C. During the heating process, weigh 9 g of Li-Ph-POSS and 100 mL of anhydrous ethanol and add them to a beaker and put in a magnet. Place the beaker on a magnetic stirrer for stirring. Set the speed to 300 r / min for 30 min. After the stirring time is up, pour the mixture of Li-Ph-POSS and anhydrous ethanol into the three-necked round-bottom flask containing carboxylated multi-walled carbon nanotubes and continue to react for 6 h. After the reaction is completed, the obtained product is filtered, and finally the filtered product is placed in an oven for drying at 60 °C for 12 h. Finally, the mass is weighed and bagged. The mass of the obtained product is 10.98 g, and the yield is 91.5%.

[0033] Figure 4 FT-IR spectra of raw material carboxylated multi-walled carbon nanotubes (MWCNTs-COOH), Li-Ph-POSS and prepared nanocomposites (CNT-POSS(Li)). 3650~3110 is the characteristic peak of carboxyl group, 3100~2980 cm -1 The multiple peaks at 1638 cm -1 C=O stretching vibration absorption peak, 1200~900 cm -1 It is the vibration absorption peak of C-Si, Si-O-Si and Si-O-Li bonds.

[0034] Figure 5 The XRD spectra of the raw material carboxylated multi-walled carbon nanotubes (MWCNTs-COOH), Li-Ph-POSS and the prepared nanocomposite (CNT-POSS(Li)) show that there are multiple diffraction peaks with weak intensity at 26.1°, which are attributed to the (002) crystal plane of hexagonal graphite in the carbon nanotubes, indicating that Li-Ph-POSS covers the surface of the carbon nanotubes, resulting in a decrease in the intensity of its diffraction peaks. When the diffraction angle is less than 20°, multiple sharp and strong diffraction peaks appear in the XRD spectrum of Li-Ph-POSS, while the position and intensity of the diffraction peaks at the corresponding position in CNT-POSS(Li) are not affected, further proving that Li-Ph-POSS covers the surface of the carbon nanotubes.

[0035] Figure 6TG spectra of raw material carboxylated multi-walled carbon nanotubes (MWCNTs-COOH), Li-Ph-POSS and prepared nanocomposite (CNT-POSS(Li)) (nitrogen atmosphere, heating rate 10 ºC / min). TG images show that CNT-POSS(Li) T 95% The temperature of the molten-carbon mixture was 344 ºC and the residual carbon at 800 ºC was 69.7 wt%, indicating that it meets the processing requirements of general polymers and has high thermal stability.

[0036] Figure 7 The scanning electron microscope and corresponding elemental surface scan of the prepared nanocomposite (CNT-POSS(Li)). The scanning electron microscope image shows that CNT-POSS(Li) has a nanotube-like morphology and the silicon element is evenly distributed on the nanotubes, proving that Li-Ph-POSS nanoparticles are successfully coated on the MWCNTs-COOH surface. Example 2

[0037] A method for preparing a carbon nanotube surface-loaded alkali metal silsesquioxane particle nanocomposite flame retardant comprises the following steps: Weigh 1 g of carboxylated single-walled carbon nanotubes (SWCNTs-COOH) and add it to a three-necked round-bottom flask. Then add 200 ml of anhydrous acetone as a solvent. Cover the three-necked round-bottom flask and start ultrasonic heating to 40 °C. During the heating process, weigh 3 g of Na-Ph-POSS and 50 mL of anhydrous acetone and add them to a beaker and put in a magnet. Place the beaker on a magnetic stirrer for stirring. Set the speed to 200 r / min and the time to 15 min. After the stirring time is up, pour the mixture of Li-Ph-POSS and anhydrous acetone into the three-necked round-bottom flask containing carboxylated single-walled carbon nanotubes and continue to react for 4 h. After the reaction is completed, the obtained product is filtered and finally placed in an oven for drying at 70 °C for 16 h. Finally, the mass is weighed and bagged. The mass of the obtained product is 3.57 g, and the yield is 89.3%. Example 3

[0038] A method for preparing a carbon nanotube surface-loaded alkali metal silsesquioxane particle nanocomposite flame retardant comprises the following steps: Weigh 1 g of carboxylated multi-walled carbon nanotubes (MWCNTs-COOH) and add them to a three-necked round-bottom flask. Then add 100 ml of chloroform as a solvent, cover the three-necked round-bottom flask and start ultrasonic heating to 40 °C. During the heating process, weigh 3 g of Li-Ph-POSS and 60 mL of chloroform and add them to a beaker and put in a magnet. Place the beaker on a magnetic stirrer for stirring. Set the speed to 400 r / min for 20 min. After the stirring time is up, pour the mixture of Li-Ph-POSS and chloroform into the three-necked round-bottom flask containing carboxylated multi-walled carbon nanotubes and continue to react for 4 h. After the reaction is completed, the obtained product is filtered, and finally the filtered product is placed in an oven for drying at 60 °C for 12 h. Finally, the mass is weighed and bagged. The mass of the obtained product is 3. 82 g, and the yield is 95.5%. Example 4

[0039] A method for preparing a carbon nanotube surface-loaded alkali metal silsesquioxane particle nanocomposite flame retardant comprises the following steps: Weigh 3 g of carboxylated single-walled carbon nanotubes (MWCNTs-COOH) and add them to a three-necked round-bottom flask. Then add 200 ml of anhydrous isopropanol as a solvent. Cover the lid of the three-necked round-bottom flask and start ultrasonic heating to 50 °C. During the heating process, weigh 6 g of Na-Ph-POSS and 100 mL of anhydrous isopropanol and add them to a beaker and put in a magnet. Place the beaker on a magnetic stirrer for stirring. Set the speed to 300 r / min and the time to 20 min. After the stirring time is up, pour the mixture of Na-Ph-POSS and anhydrous isopropanol into the three-necked round-bottom flask containing carboxylated single-walled carbon nanotubes and continue to react for 6 hours. After the reaction is completed, the obtained product is filtered and finally placed in an oven for drying at 80 °C for 15 hours. Finally, the mass is weighed and bagged. The mass of the obtained product is 7.3 g, and the yield is 81.1%.

[0040] The above is only a specific implementation of the present invention, which enables those skilled in the art to understand or implement the present invention. Although detailed descriptions are given with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions recorded in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments, and they should all be covered by the protection scope of the claims.

Claims

1. A method for preparing a carbon nanotube surface-loaded alkali metal silsesquioxane particle nanocomposite flame retardant, characterized in that: The steps include: An organic solvent and carbon nanotubes are added to a reaction container, the water bath temperature is controlled to be 40-60 ºC, the ultrasonic power is 50-100 W, and mechanical stirring is continued for 0.5-1 h. Then, alkali metal silsesquioxane powder is added to the reaction container. The reaction time is 4-12 h to obtain a gray-black mixed solution. The mixed solution is filtered, and the obtained filter cake is dried to obtain a carbon nanotube surface-loaded alkali metal silsesquioxane particle nanocomposite flame retardant.

2. The method for preparing a carbon nanotube surface-loaded alkali metal silsesquioxane particle nanocomposite flame retardant according to claim 1, characterized in that: The mass ratio of the carbon nanotube to the alkali metal silsesquioxane powder is (0.5-1):(1.2-3.6).

3. The method for preparing a carbon nanotube surface-loaded alkali metal silsesquioxane particle nanocomposite flame retardant according to claim 1, characterized in that: The organic solvent is one or more of methanol, ethanol, isopropanol, acetone, butanone, tetrahydrofuran, dichloromethane, chloroform and dimethyl sulfoxide.

4. The method for preparing a carbon nanotube surface-loaded alkali metal silsesquioxane particle nanocomposite flame retardant according to claim 1, characterized in that: The mass volume ratio of the carbon nanotubes to the organic solvent is 1-3: 150-500, and the mass volume ratio of the alkali metal silsesquioxane powder to the organic solvent is 2-9: 100-400.

5. The method for preparing a carbon nanotube surface-loaded alkali metal silsesquioxane particle nanocomposite flame retardant according to claim 1, characterized in that: The carbon nanotubes are carboxylated single-walled carbon nanotubes or multi-walled carbon nanotubes.

6. The method for preparing a carbon nanotube surface-loaded alkali metal silsesquioxane particle nanocomposite flame retardant according to claim 1, characterized in that: The alkali metal silsesquioxane is heptaphenylsilsesquioxane lithium salt or heptaphenylsilsesquioxane sodium salt.

Citation Information

Patent Citations

  • Preparation method of POSS grafted carbon nanotube composite lithium-sulfur battery diaphragm

    CN110890503A

  • Simple preparation method of polyhedral oligomeric silsesquioxane coated ammonium dinitramide

    CN116947576A

  • Chemically modified carbon nanotube, and method for producing the same

    JP2009102179A

Cited By

  • Carbon nanotube / lamellar alkali metal silsesquioxane nano-composite flame-retardant epoxy resin and preparation method thereof

    CN119639182A